Evidence for a superantigen mediated process in Kawasaki disease. Issue 4 (April 1995) - Curtis, N; Zheng, R; Lamb, J R; Levin, M
Abstract : The clinical, pathological, and immunological similarities between Kawasaki disease and the staphylococcal and streptococcal toxic shock syndromes suggest that a superantigen toxin may be involved in the pathogenesis of the disease. The V beta repertoire of peripheral blood mononuclear cells from 21 children with Kawasaki disease, 28 children with other illnesses, and 22 healthy controls were examined using monoclonal antibodies to V beta 2, 5, 8, 12, and 19. The mean percentage of V beta 2 expressing T cells in the patients with Kawasaki disease was increased when compared with healthy controls or children with other illnesses. The mean percentages of V beta 5, 8, 12, and 19 expressing T cells were also increased in the patients with Kawasaki disease compared with healthy controls, but were not increased when compared with children with other illnesses. The selective use of V beta 2 supports the hypothesis that a superantigen is involved in the pathogenesis of Kawasaki disease.